2018
DOI: 10.21067/jem.v14i1.2386
|View full text |Cite
|
Sign up to set email alerts
|

Tekanan Anggaran Waktu, Locus of Control, Kinerja dan Niat Mengundurkan Diri: Perilaku Audit Disfungsional

Abstract: This research aims to examine and to provide empirical evidence on the influence of time budget pressure, locus of control, performance and turnover intention to dysfunctional audit behavior. The dysfunctional audit behavior examined are audit quality reduction behavior (AQR) and underreporting of time (URT) behavior. This research uses survey method by using questionnaire to collect the data. The sample of this research is the auditor who work in Public Accounting Firm in East Java and are chosen by using pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
1
2
0
2
Order By: Relevance
“…The results of this study found that the time budget pressure variable has a positive and significant effect on auditory dysfunctional behavior. This is in line with research conducted by Rindawan (2018); Arsantini & Wiratmaja (2018) which found that time budget pressure has a positive and significant effect on auditory dysfunctional behavior. H6: The higher the time budget pressure felt by the auditor, the higher the tendency of the auditor to perform dysfunctional behavior.…”
Section: H3: the Higher The Time Budget Pressure Felt By The Auditor ...supporting
confidence: 91%
See 2 more Smart Citations
“…The results of this study found that the time budget pressure variable has a positive and significant effect on auditory dysfunctional behavior. This is in line with research conducted by Rindawan (2018); Arsantini & Wiratmaja (2018) which found that time budget pressure has a positive and significant effect on auditory dysfunctional behavior. H6: The higher the time budget pressure felt by the auditor, the higher the tendency of the auditor to perform dysfunctional behavior.…”
Section: H3: the Higher The Time Budget Pressure Felt By The Auditor ...supporting
confidence: 91%
“…When an auditor tends to have an external locus of control and experiences high job demands, the auditor will feel anxious and will take all actions to avoid these demands, such as dysfunctional behavior (Rindawan, 2018). In line with attribution theory, external locus of control is an internal cause that influences a person's behavior.…”
Section: H3: the Higher The Time Budget Pressure Felt By The Auditor ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Hal ini dapat disebabkan karena baik auditor yang memiliki lokus kendali internal maupun eksternal akan tetap memiliki kinerja yang baik dengan adanya pelatihan yang cukup dalam pelaksanaan penugasan audit. Hasil penelitian ini sejalan dengan penelitian (Rindawan, 2018). Kinerja adalah sesuatu untuk memenuhi tanggung jawabnya dalam menjalankan tugas, sehingga auditor dapat melakukan beberapa cara alternative yang bisa digunakan untuk memenuhi tanggung jawabnya tersebut (Zaharuddin, Supriyadi, & Wahyuningsih, 2021)…”
Section: Pengaruh Kinerja Terhadap Penerimaan Disfungsional Auditunclassified
“…Di samping locus of control, komitmen auditor terhadap profesi yang ditekuninya adalah faktor penting yang berdampak pada perilaku auditor saat berhadapan dengan isu-isu etis ketika menjalankan tugas audit. Sementara penyebab eksternal lebih tertuju pada lingkungan yang berdampak pada perilaku individu (Rindawan, 2018). Adanya anggaran waktu yang ketat cenderung menjadi tekanan bagi seorang auditor dalam melakukan penugasan audit, karena auditor dituntut agar mampu menghasilkan laporan keuangan yang berkualitas disertai dengan anggaran waktu yang terbatas.…”
Section: Pendahuluanunclassified